Opening van het afdelingskantoor aan de Hemonylaan 24. Voorzitter Van Eerde achter zijn bureau - Nieuwenhuijs, Henk
Opening van het afdelingskantoor aan de Hemonylaan 24. Voorzitter Van Eerde achter zijn bureau.